The role of Sphingolipids in myelination and myelin stability and their involvement in childhood and adult demyelinating disorders. Issue 4 (25th August 2020) - Giussani, Paola; Prinetti, Alessandro; Tringali, Cristina
Abstract: Multiple sclerosis (MS) represents the most common demyelinating disease affecting the central nervous system (CNS) in adults as well as in children. Furthermore, in children, in addition to acquired diseases such as MS, genetically inherited diseases significantly contribute to the incidence of demyelinating disorders. Some genetic defects lead to sphingolipid alterations that are able to elicit neurological symptoms. Sphingolipids are essential for brain development, and their aberrant functionality may thus contribute to demyelinating diseases such as MS. In particular, sphingolipidoses caused by deficits of sphingolipid‐metabolizing enzymes, are often associated with demyelination. Sphingolipids are not only structural molecules but also bioactive molecules involved in the regulation of cellular events such as development of the nervous system, myelination and maintenance of myelin stability. Changes in the sphingolipid metabolism deeply affect plasma membrane organization. Thus, changes in myelin sphingolipid composition might crucially contribute to the phenotype of diseases characterized by demyelinalization. Here, we review key features of several sphingolipids such as ceramide/dihydroceramide, sphingosine/dihydrosphingosine, glucosylceramide and, galactosylceramide which act in myelin formation during rat brain development and in human brain demyelination during the pathogenesis of MS, suggesting that this knowledge could be useful in identifying targets for possible therapies. Abstract : We examined the recent literature concerning the impact of sphingolipid and sphingoid alterations on demyelinating disorders in childhood (sphingolipidoses) and adults (multiple sclerosis). We underline some common phenotype facets and genetic defects among these types of disorders so different, but both showing essential defects in myelin stability. Then, we explored the importance of sphingolipids and sphingoid molecules for myelin formation and stability. We think that this review could help to highlight these results and to recognise the role of sphingolipid metabolism defects in demyelinating disorders, stimulating novel cues of research.